Links Between Ethylene and Sulfur Nutrition—A Regulatory Interplay or Just Metabolite Association? - Wawrzynska, Anna; Moniuszko, Grzegorz; Sirko, Agnieszka (Frontiers in Plant Science, 2015)
Multiple reports demonstrate associations between ethylene and sulfur metabolisms, however the details of these links have not yet been fully characterized; the links might be at the metabolic and the regulatory levels. First, sulfur-containing metabolite, methionine, is a precursor of ethylene and is a rate limiting metabolite for ethylene synthesis; the methionine cycle contributes to both sulfur and ethylene metabolism. On the other hand, ethylene is involved in the complex response networks to various stresses and it is known that S deficiency leads to photosynthesis and C metabolism disturbances that might be responsible for oxidative stress. In several plant species, ethylene increases during sulfur starvation and might serve signaling purposes to initiate the process of metabolism reprogramming during adjustment to sulfur deficit. An elevated level of ethylene might result from increased activity of enzymes involved in its synthesis. It has been demonstrated that the alleviation of cadmium stress in plants by application of S seems to be mediated by ethylene formation. On the other hand, the ethylene-insensitive Nicotiana attenuata plants are impaired in sulfur uptake, reduction and metabolism, and they invest their already limited S into methionine needed for synthesis of ethylene constitutively emitted in large amounts to the atmosphere. Regulatory links of EIN3 and SLIM1 (both from the same family of transcriptional factors) involved in the regulation of ethylene and sulfur pathway, respectively, is also quite probable as well as the reciprocal modulation of both pathways on the enzyme activity levels.